Análisis comparativo de la riqueza nutricional de tres tipos de estiércoles producidos en dos fincas de productores agropecuarios de la provincia de Zamora Chinchipe - Romero Cobos, David Salustino (2016)
The study "Comparative analysis of the nutritional richness of three types of manures produced in two farms of agricultural producers in the province of Zamora Chinchipe" was born with the idea of knowing the nutritional content of manures and the possibility of using them as raw material for use and exploitation. According to the diagnosis made to each of the farms, because "Pamela" Farm has less number of animals and also have a subsistence economic sustainability, it is different in its objective than "La Española" Farm, which has commercial orientation of work to have Better operational management, greater investment in infrastructure and more animals. As for scientific literature, for this subject there is valuable information both in textbooks and on the internet, so the bibliography has been taken mostly through this medium, but also some very valuable texts. The methodology used in this study is based on field observation, data collection in the agricultural units themselves and in research through surveys and laboratory tests. In addition, the Olivera Methodology, 2003, was used to determine sustainability of the farm. The most important results of the study are: on the farms the same species are produced under a different breeding and feeding system; Parallel to this, the application of the matrices of the five subsystems to characterize the farms allowed to determine that the farms, are in an average sustainable management, because certain indicators of the subsystems were rated with a low or medium level; On the other hand the results of the parameters analyzed in the manure samples of each species show that certain parameters are high on one farm and low on the other farm or vice versa. Thus, it is concluded that the characteristics of each farm and the breeding and feeding system of the species influence the results of the analysis of the manure samples, obtaining that: in the Pamela farm the manure with the highest nutritional potential is the Pigs with a percentage of 45.1%, as in the Española farm, the manure with the highest nutritional potential is the pig with a percentage of 40.9%; With reference to the analyzed parameters.